Comparative investigation of medical contents using desktop and tabletop technologies - Madni, T.M. (Springer Verlag, 2015)
In recent years, in the field of human-computer interaction show that interactive technologies, constructive methods and appropriate interfaces have great impact in improving learning and creative education. Such interactive technologies along with suitable interfaces are beneficial for humans in various domains especially in the field of healthcare. Generally, in practice, medical monitoring and diagnosis systems are based on desktop computers and have been less explored on multi-touch tabletops. It is due to its less availability but supports collaborative activities and natural form of interaction. This paper presents an experimental investigation of technological-based comparative study, with collaborative activities using desktop technologies and tabletop technologies. A prototype was implemented based on the proposed conceptual framework. Furthermore, a quantitative investigation on the usefulness of these technologies was conducted with twenty students. The experiment showed investigation of medical elements, was more significant in tabletop technologies as compared to desktop technologies. Â© Springer-Verlag Berlin Heidelberg 2015.